Wraig Ar Lan Yr Afon, Y - Williams, Aled Jones (Gwasg Carreg Gwalch, 2020)
The author introduces his latest novel as: 'Some form of thriller, or at least a work that uses thriller conventions. In more simple terms, it is about a woman moving to live from here to nowhere and the implications of that move. Intro – Teitl – Hawlfraint – Cyflwyniad – Y Diwedd (1) – Y Dechreuad – Y Diwedd (2) – Efallai – Nofel arall gan Aled Jones Williams.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books